Microscopic Characteristics Of Emu (Dromaius Novaehollandiae) Semen Collected By Non-Teaser Method In Humid Tropical Climate - Sundaresan, A.; Omprakash, A.V.; Ezhilvalavan, S.; Pandian , C. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was conducted for collection and evaluation of Emu bird semen by non teaser method. The raw semen collected from individual Emu birds was evaluated for microscopical seminal attributes. Highly significant (P<0.001) results were obtained and the overall mean values for mass activity, per cent motility, concentration, per cent live and abnormal spermatozoa of individual male was 3.36 ± 0.08, 74.39+0.99, 2.19+0.05 x109per ml, 87.40±0.67 % and 9.15 ± 0.33 % respectively. The individual males showed varied response and significant difference in seminal attributes. Creamy white thick consistency semen had significant (P<0.01) seminal attributes than yellow and watery semen.